Abastecimento de água na cidade de Marabá - Pará - MORAES, Lindalva Canaan Jorge (Universidade Federal do Pará, 2018)
This work analyzes the formation, expansion and management of the water supply system of the city of Marabá, in the State of Pará. In the mid-‘70s, the city became the locus of a strong demographic growth, exacerbated by an intensive migration process, resulting from several public initiatives connected with a policy of national integration This policy comprised the development of infrastructure such as roads, hydroelectric plants, official colonization plans, implementation of big projects, as the mining complex of Carajas, incentives to agriculture and cattle-raising and timber exploration. This demographic boom increased by four times the city’s urban population creating a big impact in the supply of public services, overburdening, inclusive, the water supply system. Aiming to contribute to the debate on the question of water supply in the aforementioned city, we concentrated our efforts to analyze how the city’s water supply is being made throughout these years. Its present supply structure, which areas are covered by the services provided by the Company of Water Supply of the State of Pará and which are not and which alternatives of water supply are being adopted to secure water supply services in areas not covered by the official water supply system.